Notre terre vue du ciel - Stéphanie Tselouiko (Revue d'ethnoécologie)
In this article I propose to highlight the mechanisms of transcription and translation of a territorial knowledge incorporated into words and symbols projected on maps and associated new discourses. As a first step, an analysis of how the Xikrin of the Trincheira Bacajá Indigenous Land (Pará, Brazil) relate to their surrounding forest world will allow me to argue that territoriality and learning go hand in hand with the production of sociality that is concretized in the displacement through the forest and the appropriation of species and spaces. Then, in a second step, I will try to show that a new knowledge, always open, is created from the codification and transformation of the forest into a map. Finally, I will show how, on the basis of this transformation, the relational and affective processes that define territoriality give rise to a new conception of territory as a political object.